Ecology and management of tropical secondary forest: Science, people, and policy - Guariguata, Manuel R. Finegan, Bryan (Costa Rica : CATIE, 1998)
Research in tropical forestry is confronted with the task of finding strategies to alleviate pressure on remaining forests, and techniques to enhance forest regeneration and restore abandoned lands, using productive alternatives that can be attractive to local human populations.
1. Land use policy and secondary forest management in the notern zone of Costa Rica 2. Dynamics de sementes e regeneracao
incluye índice
Col. Agro
Keywords: 1. ECOLOGY AND SILVICULTURE 2. ABUNDANCE AND DIVERSITY OF USEFUL WOODY